Optimising patient engagement for assessing total joint arthroplasty outcomes – a randomised controlled trial - Wyatt Tyndall; Nebojsa Kuljic; Michael Thatcher; Michaela Nickol; Johannes M. van der Merwe (Journal of Orthopaedic Surgery and Research)
Abstract Introduction Patient satisfaction is a critical outcome in total joint arthroplasty (TJA), yet assessing it effectively remains a challenge due to limitations in patient-reported outcome measures (PROMS). While these measures are commonly gathered in clinical settings, additional contact through mail or phone is often needed, and low response rates can affect the validity and reliability of collected data. To improve response rates, this study evaluated various methods of incentivizing patient participation in a randomized trial format, focusing on postal questionnaires. Patients and methods The study investigated three methods to improve response rates: including a gift card with the questionnaire, promising a gift card upon questionnaire completion, and offering no incentive. It also examined whether different monetary values and the inclusion of the surgeon’s name on materials impacted response rates. We tried to determine factors that could improve follow up telephone response rates in the group of patients that failed to return their questionnaires. Results Higher response rates were observed with monetary incentives (P = 0.056), larger amounts of money offered (P = 0.3839) for filling out the questionnaire, and if the surgeon’s details were on the cover letter or questionnaire (P = 0.632). There was no correlation between age and sex and participation. We did find a statistically significant difference in total participation and poorer total knee arthroplasty outcomes scores (P < 0.001). Conclusion Our study supports findings from prior research indicating that monetary incentives and personalized materials can improve response rates, although in this cohort, results were modest. Follow-up calls further boosted response rates, suggesting that multi-modal engagement may be beneficial. Although the response improvements were limited and lacked statistical significance, the study highlights the importance of refining strategies to ensure reliable PROMS data, which is vital for understanding patient outcomes in TJA. Future studies might consider demographic factors and other outreach methods to enhance PROMs data collection.